AB0946 PARTICULARITY OF MULTIFOCAL INFECTIOUS SPONDYLODISCITIS. (2nd June 2020) - Miladi, S.; Saadaoui, K.; Fazaa, A.; Mariem, S.; Ouenniche, K.; Souabni, L.; Kassab, S.; Chkili, S.; Zakraoui, L.; Laatar, A.
Abstract : Background: Infectious spondylodiscitis is an infection of the intervertebral disc with damage to the vertebrae. Multiple stage involvement may lead to serious complications. Better understand of this infection is mandatory for optimal management. Objectives: The objective of our study was to describe the clinical, biological aspects and the course of this disease. Methods: This is a retrospective study including cases of infectious spondylodiscitis collected in a single rheumatology center between 2002 and 2018. Multi focal spondylodiscitis was defined as an attainment of 2 or more disc levels. Clinical, biological and evolution of this disease were reported. Results: Among the 52 cases of infectious spondylodiscitis collected, thirteen patients had multi-stage involvement of the spine. The sex ratio M/F in this group = 0.44 with an average age of 52 ± 14.32 years [31 – 76 years]. Diabetes mellitus was observed in 3 patients, chronic renal failure in one case and immunosuppressive therapy in one case. At the moment of the diagnosis, inflammatory back pain was present in all patients, fever was noted in 8 patients (61.5%), neurological deficit in 2 patients (15.4%) and weight loss in 4 cases (30.8%). The diagnosis time delay was 22 ± 15.9 weeks [2 – 60 weeks]. The mean CRP was 70.16 mg / L ± 55.5 [3.4 - 178] and the ESR was on average 79 mm ± 31.28 [6 - 125]. Diagnosis was confirmed by MRI in all cases. A prevertebral abscess was observed in 7 cases (%), an epiduritis in 5 patients (38.5%) and a psoas abscess in two cases (15.2%). The cervical spine was affected in 3 cases, the dorsal spine as well as the lumbar spine were affected in 12 cases. The involvment of 2 vertebral sites was the most frequent with 7 cases. A maximum of 5 site was noted in 3 cases. The thoracolumbar spine was the most affected with 11 cases (84.6%), the cervico-thoraco-lumbar involvement was found in only one case (7.7%). The bacteriological diagnosis was done by the disco-vertebral biopsy in 6 cases (46.2%), the brucellar serology in 3 cases (26.1%) and a strong presumption of tuberculosis (with positive IDR or Quantiferon) in 4 cases (30.8%). Mycobaterium tuberculosis was isolated in 8 patients (61.5%), brucella melitensis in 3 patients (23.1%) and staphylococcus aureus was found in 2 cases (15.4%). The outcome was favorable in all patients with appropriate antibiotic therapy after an average follow-up of 10.9 months ± 2.19. Conclusion: Multifocal infectious spondylodiscitis is a serious disorder which mainly affects immunocompromised patients and the specific germs are the most incriminated. Disclosure of Interests: None declared